ELIGIBILITY OF ELECTRONIC SIGNATURE WHEN APPLYING HOME OWNERSHIP CREDIT (KPR) AT THE BANK ACCORDING TO CIVIL LAW - Denny Yanuar Setyo Laksono (Hang Tuah Law Journal, 2021)
Home Ownership Credit (KPR) is an important thing in making it easier for people to have housing for those who have small and medium economic income. Housing loans are one of the Bank's products that are related to the level of demand for housing, in this case following the interest rates that affect housing demand. Therefore, innovation is needed to make it easier for people to have housing. The Bank's innovation is to use electronic signatures as a more efficient form of transaction. This research is a juridical-normative research using a statutory approach. The legal issue that is used as a problem formulation is divided into two, namely whether the electronic signature at the time of submitting a Home Ownership Credit (KPR) at a bank is valid according to civil law and whether the impact of an application for a Home Ownership Credit (KPR) agreement made using an electronic signature. The results of this research are electronic signatures or electronic transactions on applications for Home Ownership Credit (KPR) are basically related to an engagement or a legal relationship in accordance with Law No. 11 of 2008 concerning electronic information and transactions and the third book of the Civil Code on Engagement. The impact resulting from the change of Signatures in front of Notary Officers to become Electronic Signatures has the same legal force to bind one another in accordance with Law No. 4 of 1996 concerning Mortgage Rights to Land and objects related to Land and Law No. 11 of 2008 concerning Electronic Information and Transactions, the regulation stipulates that Electronic Signatures are Legitimate according to Civil Law.